A Comparison of American and Chinese Consumers’ Attitudes Toward Athlete Celebrity Endorsers - Alan D. Schaefer; R. Stephen Parker; John L. Kent (Journal of Applied Sports Management, 2010)
China is home to one of the fastest growing sport industries in the world (Yang, Sparks, & Li, 2008). To reach this market, international marketers are increasingly turning to athlete celebrity endorsers (ACEs) (Tschang, 2009). However, little is known about Chinese consumers’ receptiveness to this strategy. The purpose of this study is to test for differences between Chinese and U.S. consumers’ general attitudes towards ACEs. Results from a classroom administered survey of 147 college students in the U.S. and China provide insight into how consumers in those two nations differ in their responsiveness to ACEs.
Keywords: Celebrities; Endorsements; Spokespersons; Advertising; Athletes; China; Consumer attitudes; Global